Advice for analytic naturalists - Hambly, Jesse (Ergo, 2022)
In this paper I argue against Analytic Normative Naturalism by suggesting that the view cannot capture the way that normative concepts figure in advice. To establish this conclusion, I identify several links between normative concepts and advice and argue that, if Analytic Normative Naturalism were true, these links would not obtain.
Gesehen am 09.02.2026